1T‐Phase WS2 Protein‐Based Biosensor. (27th December 2016) - Toh, Rou Jun; Mayorga‐Martinez, Carmen C.; Sofer, Zdenek; Pumera, Martin
Abstract : Metallic 1T‐phase transition metal dichalcogenides have been recognized for their desirable properties like high surface‐to‐volume ratio, high conductivity, and capacitive behavior, making them outstanding for catalytic and sensing applications. Herein, a hydrogen peroxide (H2 O2 ) biosensor is constructed by the immobilization of hemoglobin (Hb) on 1T‐phase WS2 (1T‐WS2 ) sheets, and entrapment by glutaraldehyde. 1T‐WS2 not only displays electrocatalytic activity toward the reduction of H2 O2 but also provides a high surface‐to‐volume ratio and conductive platform for the immobilization of Hb and facilitation of its electron transfer to the electrode surface. The advantageous role of 1T‐phase WS2 is further demonstrated for the construction of a heme‐based H2 O2 biosensor compared to its 1T‐phase MoS2, MoSe2, and WSe2 counterparts. Synergistic interactions between 1T‐WS2 and Hb result in a H2 O2 biosensor with high analytical performance in terms of wide range, sensitivity, selectivity, reproducibility, repeatability, and stability. These findings have profound impact in the research fields of electrochemical sensing and biodiagnostics. Abstract : Synergistic effects between 1T‐phase WS2 and hemoglobin result in a high‐performing hydrogen peroxide (H2 O2 ) biosensor compared to its 1T‐phase MoS2, MoSe2, and WSe2 counterparts. 1T‐phase WS2 displays electrocatalytic activity toward the reduction of H2 O2 and serves as a high surface‐to‐volume ratio and conductive platform for hemoglobin immobilization and facilitation of its electron transfer to the electrode surface.